Sample preparation method for analyzing morphology of section microstructure of optical film
By using a transparent PET protective film to cover the optical film sample and cut it quickly, the problem of long sample preparation time and low efficiency in the existing metallographic sample preparation methods is solved, and the sample preparation efficiency and the improvement of cross-sectional quality are achieved.
Patent Information
- Application Number
- CN202411989046.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing metallographic sample preparation method has a long time and low efficiency in the microstructure morphology analysis of optical film sections, making it difficult to meet the requirements for analytical aging in industrial production.
The transparent PET protective film is used to cover the optical film sample to be measured, and the sample with a clear and complete cross-sectional microstructure morphology is obtained.
It effectively shortens the sample preparation time, improves the operation and analysis efficiency, solves the cumbersome and time-consuming problems of traditional metallographic samples, and has the characteristics of fast sample preparation efficiency and high cross-sectional quality.
Smart Images

Figure CN119827250A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical films, and in particular to a sample preparation method for analyzing the microstructure morphology of an optical film cross section. Background Art
[0002] The optical film of the backlight module in a common liquid crystal display module generally includes a diffusion film and a brightness enhancement film as well as a composite film formed by the combination of these two films. Among them, the brightness enhancement film is generally composed of a first layer of substrate, a second layer of anti-scratch coating laminated on one side and a third layer of prism layer laminated on the other side. With the help of the convergence effect of the microstructure in the prism layer on light, the brightness of the backlight module under the positive viewing angle can be effectively increased, thereby improving the energy efficiency of the entire liquid crystal display module. In particular, the structural parameters such as the period and vertex angle of the microstructure of the prism layer are key factors affecting the light convergence effect.
[0003] Therefore, in the manufacturing process of brightness enhancement film, microstructure parameters are an important optical indicator. At the same time, considering that the manufacturing of brightness enhancement film generally adopts a roll-to-roll continuous production process, how to ensure the timeliness of the test and reduce material waste are also indicators that need to be considered.
[0004] Metallographic analysis is a common method in materials science for analyzing the microstructure, elements and composition of materials. It is also applicable to the morphology analysis of optical film microstructures. However, it is first necessary to perform "metallographic sample preparation" on the samples to be tested and analyzed, and then spray gold and place them in an electron microscope for observation, analysis and measurement.
[0005] Existing metallographic sample preparation methods usually include the following four steps:
[0006] First, a larger sample (e.g., an optical film with a plastic film as a substrate (polymethyl methacrylate PMMA, triacetate TAC, super phase retardation film SRF, polyethylene terephthalate PET, etc.)) is cut to obtain a sample of appropriate size;
[0007] Second, place the sample cut in step 1 into a commercial mounting machine filled with resin;
[0008] Third, after the resin is fully cured, remove the resin embedded with the sample from the mold;
[0009] Fourth, use a grinding and polishing machine or manually grind and polish the sample obtained in step 3 to prepare a metallographic sample to be observed.
[0010] Usually, the resin used for embedding samples in the metallographic sample preparation process is epoxy resin, which takes 6-8 hours to fully cure at room temperature. Even if high-temperature curing is used, it still takes 2-4 hours.
[0011] Therefore, although metallographic sample preparation can obtain metallographic samples of good quality, the preparation process of this method is cumbersome, time-consuming, and has low analysis efficiency. It is not conducive to quickly obtaining test data and it is difficult to meet the requirements of analysis and characterization timeliness in industrial production.
[0012] In view of this, the present invention is proposed. Summary of the invention
[0013] The object of the present invention is to provide a sample preparation method for optical film cross-sectional microstructural morphology analysis. Compared with the traditional metallographic sample preparation method, the sample preparation method effectively shortens the sample preparation time, improves the operation and analysis efficiency, alleviates the problems of cumbersome and time-consuming sample preparation process in the existing metallographic analysis, and has the characteristics of fast sample preparation efficiency and high cross-sectional quality.
[0014] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0015] The present invention provides a sample preparation method for optical film cross-section microstructure morphology analysis, the sample preparation method comprising:
[0016] S1: Provide the optical film sample and PET protective film to be tested;
[0017] S2: peeling off the release layer of the PET protective film, and then laminating the adhesive surface of the PET protective film with the microstructure surface of the optical film sample to be tested to obtain a coated sample to be tested;
[0018] The PET protective film comprises a transparent protective film layer, a glue layer and a release layer arranged in sequence;
[0019] The transmittance of the transparent protective film layer of the PET protective film is greater than 89%, and the haze is less than 2%, and the viscosity of the PET protective film is 3 to 25 gf / 25 mm;
[0020] S3: confirm the extension direction of the microstructure on the coated sample by microscopic observation, and cut along the extension direction of the microstructure to obtain the optical film strip;
[0021] S4: The optical film strip is attached to the cutting pad and fixed, and then two L-shaped fixing brackets are fixed above the optical film strip; the position of one of the L-shaped brackets is adjusted, and the angle between the blade and the film is adjusted to 90°. A 1kg weight is used to quickly smash down from top to bottom at a position about 5 to 10 cm above the blade, and the acceleration of the blade is 2.5-5cm / s 2 , obtaining the cut optical film splines;
[0022] During the cutting, the transparent protective film layer is arranged below the optical film sample to be tested;
[0023] S5: Peeling off the transparent protective film layer to obtain an optical film strip having a cross-sectional microstructure.
[0024] Furthermore, the optical film sample to be tested includes any one of a 3D grating film with a microstructure, a wide-viewing angle film, a light-homogenizing film, and a brightness-enhancing film.
[0025] Furthermore, the transparent protective film layer of the PET protective film has a thickness of 38 to 100 μm.
[0026] Furthermore, the adhesive layer thickness of the PET protective film is 5 to 20 μm.
[0027] Furthermore, the adhesive system of the PET protective film is one of acrylic, polyurethane or silicone systems;
[0028] Preferably, the adhesive system of the PET protective film is a polyurethane system.
[0029] Furthermore, after the PET protective film is attached to the optical film sample to be tested, the peeling force at 180° is 3-25 gf / 25 mm.
[0030] Furthermore, the size of the optical film strip is 100 mm*10 mm.
[0031] The sample preparation method for optical film cross-sectional microstructure morphology analysis provided by the present invention is applied in optical film cross-sectional microstructure morphology analysis.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The sample preparation method for optical film cross-sectional microstructure morphology analysis provided by the present invention first covers the microstructure surface of the optical film sample to be tested with a layer of transparent PET protective film, and then uses a sharp blade to cut the coated optical film to quickly obtain a sample with a clear and complete cross-sectional microstructure morphology. Compared with the traditional metallographic sample preparation method, the sample preparation method of the present application effectively shortens the sample preparation time, improves the operation and analysis efficiency, alleviates the problems of cumbersome and time-consuming sample preparation process in the existing metallographic analysis, and has the characteristics of fast sample preparation efficiency and high cross-sectional quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1Schematic diagram of the optical film sample to be tested, the transparent PET protective film and the transparent glass required for the sample preparation method provided in Example 1 of the present invention;
[0036] Figure 2 Schematic diagram of the side view and top view of the optical film sample to be tested after being fixed provided in Example 1 of the present invention;
[0037] Figure 3 A schematic diagram of a process of laminating an optical film with a PET protective film provided in Example 1 of the present invention;
[0038] Figure 4 A schematic diagram of a sample provided in Example 1 of the present invention after being coated with a PET protective film and cut into strips;
[0039] Figure 5 A schematic diagram of the structure of a cut optical film spline provided in Example 1 of the present invention;
[0040] Figure 6 This is a schematic diagram of the structure for fixing and detecting optical film strips provided in Example 1 of the present invention.
[0041] Icons: 01-optical film; 01a-microstructure; 01b-brightness enhancement film substrate; 01c-back coating; 02-PET protective film; release film-02a; 02b-adhesive layer; 02c-protective film substrate; 03-flat transparent glass; 04-lamination platform; 05-transparent tape; 06-handheld lamination roller; 07-mechanical roller; 08-cutting coated strips; 09-L-shaped fixing bracket; 10-blade; 11-cutting gasket; 12-weight; 13-cutting strips. DETAILED DESCRIPTION
[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] According to one aspect of the present invention, a sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01 is provided, the sample preparation method comprising:
[0044] S1: Provide the optical film 01 sample to be tested and the PET protective film 02;
[0045] S2: peel off the release layer of the PET protective film 02, and then laminate the adhesive layer 02b surface of the PET protective film 02 with the microstructure 01a morphological surface of the optical film 01 sample to obtain a coated sample to be tested;
[0046] The PET protective film 02 comprises a transparent protective film layer, a glue layer 02b and a release layer arranged in sequence;
[0047] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%. The adhesion of the PET protective film 02 to the attached test sample is 3 to 25 gf / 25 mm.
[0048] S3: confirm the extension direction of the microstructure 01a on the coated sample by microscopic observation, and cut along the extension direction of the microstructure 01a to obtain the optical film 01 strip;
[0049] S4: The optical film 01 strip is attached to the cutting pad and fixed, and then two L-shaped fixing brackets are fixed above the optical film 01 strip; the position of one of the L-shaped brackets is adjusted, and the angle between the blade 10 and the film is adjusted to 90°. A 1kg weight 12 is used to quickly smash down from about 5 to 10 cm above the blade 10, and the acceleration of the blade 10 is 2.5-5 cm / s. 2 Obtaining the cut optical film 01 spline;
[0050] During the cutting, the transparent protective film layer is arranged below the optical film 01 sample to be tested;
[0051] S5: Peeling off the transparent protective film layer to obtain an optical film 01 strip having a cross-sectional microstructure 01a.
[0052] The sample preparation method for analyzing the cross-sectional microstructure 01a of an optical film 01 provided by the present invention first covers the microstructure 01a surface of the optical film 01 sample to be tested with a layer of transparent PET protective film 02, and then uses a sharp blade 10 to cut the covered optical film 01 to quickly obtain a sample with a clear and complete cross-sectional microstructure 01a morphology. Compared with the traditional metallographic sample preparation method, the sample preparation method of the present application effectively shortens the sample preparation time, improves the operation and analysis efficiency, alleviates the problems of cumbersome and time-consuming sample preparation process in the existing metallographic analysis, and has the characteristics of fast sample preparation efficiency and high cross-sectional quality.
[0053] At the same time, the method and process adopted by the present invention are simple to operate, and samples with high-quality cross-sectional microstructure 01a morphology can be prepared after simple training of sample preparation personnel.
[0054] It should be noted that the PET protective film 02 of the present application uses a PET protective film 02 with high transmittance and low haze, so as to more clearly determine the extension direction of the microstructure 01a after the labeling.
[0055] Preferably, the transmittance of the PET protective film 02 is greater than 89%, and the haze is less than 2%. When the transmittance of the PET protective film 02 is less than 89%, or the haze is greater than 2%, it is not conducive to confirming the extension direction of the microstructure 01a of the optical film 01 after coating.
[0056] In a preferred embodiment of the present invention, the optical film 01 sample to be tested includes any one of a 3D grating film, a wide-viewing angle film, a light homogenizing film, and a brightness enhancement film having a microstructure 01a.
[0057] In a preferred embodiment of the present invention, the transparent protective film layer of the PET protective film 02 has a thickness of 38 to 100 μm, and the adhesive layer 02 b of the PET protective film 02 has a thickness of 5 to 20 μm.
[0058] As a preferred embodiment, the thickness of the transparent protective film layer and the adhesive layer 02b can, on the one hand, fully fix the microstructure 01a, and on the other hand, prevent excessive adhesive layer 02b from overflowing during the cutting process and causing contamination of the microstructure 01a.
[0059] In a preferred embodiment of the present invention, the adhesion of the PET protective film 02 is 3-25 gf / 25 mm.
[0060] In a preferred embodiment of the present invention, the adhesive system of the PET protective film 02 is one of acrylic, polyurethane or silicone systems;
[0061] In the above preferred embodiment, the adhesive system of the PET protective film 02 is a polyurethane system.
[0062] As a preferred embodiment, the PET protective film 02 of the present invention is preferably a polyurethane system and a silicone system PET protective film 02. The polyurethane system PET protective film 02 has good exhaust performance, which can effectively prevent the formation of fine bubbles after coating, resulting in the inability to clearly identify the extension direction of the microstructure 01a under a microscope, thereby causing deviations in the sample preparation process.
[0063] More preferably, in order to facilitate the distinction of the extension direction of the microstructure 01a after bonding, a silicone system with a lower refractive index is preferably used as the protective film adhesive system used in the present invention to enhance the recognition of the adhesive layer 02b of the PET protective film 02 and the microstructure 01a under a microscope.
[0064] In a preferred embodiment of the present invention, the 180° peeling force of the PET protective film 02 after being attached to the optical film 01 sample to be tested is 3 to 25 gf / 25 mm. This peeling force selection can effectively prevent the protective film from peeling off during the alignment, cutting and transfer of the sample, which affects the success of sample preparation.
[0065] In a preferred embodiment of the present invention, the size of the optical film 01 strip is 100 mm*10 mm.
[0066] According to one aspect of the present invention, the sample preparation method for analyzing the morphology of the cross-sectional microstructure 01 a of the optical film 01 can be widely used in analyzing the morphology of the cross-sectional microstructure 01 a of the optical film 01 .
[0067] The technical solution of the present invention will be further described below in conjunction with embodiments.
[0068] The following examples use a commercially available brightness enhancement film material as an example to verify the sample preparation method for analyzing the morphology of the cross-sectional microstructure 01a of the optical film 01 of the present application. That is, the optical film 01 sample to be tested in the following examples is a commercially available brightness enhancement film material, and the optical microstructure 01a used is an isosceles right triangle with a period of 50um and a vertex angle of 90°.
[0069] Example 1
[0070] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0071] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0072] Figure 1 Schematic diagram of the optical film sample 01 to be tested, the transparent PET protective film 02 and the transparent glass required for the sample preparation method of this embodiment. Figure 1 (a) is a schematic diagram of the structure of the top view and the side view of the brightness enhancement film; the brightness enhancement film includes an optical film 01, a microstructure 01a, a brightness enhancement film substrate 01b and a back coating 01c. Figure 1 (b) is a schematic diagram of the top view and side view of the PET protective film 02; the PET protective film 02 includes a release film 02a, an adhesive layer 02b, and a protective film substrate 02c. Figure 1 Middle (c) is flat transparent glass 03.
[0073] The transparent PET protective film 02 is a silicone-based PET protective film 02 (Penglin PLSAT-PAD04), the base material (transparent protective film layer) of the silicone-based PET protective film 02 is 50um, and the thickness of the adhesive layer 02b is 5um.
[0074] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0075] 2. Place the transparent glass on a flat bonding platform 04, then place the optical film 01 sample with the microstructure 01a facing upward on the transparent glass, and fix the front end with a transparent tape 05. Figure 2 shown.
[0076] Figure 2 Schematic diagram of the side view and top view of the optical film 01 sample to be tested after being fixed.
[0077] Figure 2 (a) is a side view of the optical film 01 sample to be tested after being fixed. Figure 2 (b) is a top view of the optical film 01 sample to be tested after being fixed.
[0078] 3. Tear off the release film 02a of the transparent PET protective film 02, so that the adhesive layer 02b of the PET protective film 02 faces the surface to be bonded with the optical film 01 sample, and use a handheld bonding adhesive roller 06 to stick the PET protective film 02 to the front part of the optical film 01, and then roll and bond. Figure 3 shown.
[0079] Figure 3 This is a schematic diagram of the process of laminating the optical film 01 with the PET protective film 02 in this embodiment. Figure 3 (a) is a schematic diagram of the process of manually laminating the optical film 01 with the PET protective film 02 in this embodiment. Figure 3 (b) is a schematic diagram of the process of laminating the optical film 01 with the PET protective film 02 by the laminating machine in this embodiment.
[0080] 4. Turn on the switch of the automatic laminating machine, set the laminating pressure in the range of 0.1-0.3Mpa, the laminating line speed in the range of 100-300mm / min, and use the mechanical rubber roller 07 to laminate the optical film 01 sample. Figure 3 As shown in (b).
[0081] 5. Take the optical film 01 sample obtained in step 4 and place it under an optical microscope. Observe it from the transparent PET protective film 02 surface to confirm and mark the extension direction of the microstructure 01a in the optical film 01. Figure 4 As shown in (a).
[0082] Figure 4 This is a schematic diagram of the sample after the PET protective film 02 and the optical film 01 are attached and cut into strips in this embodiment. Figure 4 (a) is a schematic diagram of a sample coated with a PET protective film 02 and an optical film 01;
[0083] Figure 4 (b) is a schematic diagram of the sample after being cut into strips.
[0084] 6. Cut along the extension direction to obtain a 100mm*10mm long and wide optical film 01 spline, wherein the length direction is along the extension direction of the microstructure 01a, and the width direction is a direction orthogonal to the extension direction of the microstructure 01a, to obtain a cut and covered spline 08. Figure 4 As shown in (b).
[0085] 7. Use transparent tape 05 to evenly attach the optical film 01 strip to a cutting pad (commercially available PVC soft rubber pad), and then fix two L-shaped fixing brackets 09 on the top of the optical film 01 strip, leaving a gap in the middle that is slightly wider than the thickness of the blade 10, and set a cutting pad 11 below. Figure 5 As shown in (a).
[0086] Figure 5 This is a schematic diagram of the structure of the cut optical film 01 strip provided in this embodiment. Figure 5 (a) is a schematic diagram of the top view of the cut optical film 01 strip; Figure 5 (b) is a schematic diagram of the side view structure of the cut optical film 01 strip.
[0087] 8. Take a commercially available blade 10 (LEICA818, 80mm long * 14mm wide * 0.35mm thick), adjust the position of one of the L-shaped fixing brackets 09, adjust the angle between the blade 10 and the diaphragm to 90°, use a 1kg weight 12 to quickly hit it from top to bottom about 5-10cm above the blade 10, and obtain the cut specimen 13, as shown in Figure 5 As shown in (b);
[0088] 9. After peeling off the PET transparent protective film, fix the optical film 01 sample on the fixture and use the Keyence microscope VK-X1000 to analyze the cross-sectional morphology. Figure 6 shown.
[0089] Figure 6 It is a schematic diagram of the structure for fixing and detecting the optical film 01 spline. Figure 6 (a) is a schematic diagram of a top view structure for fixing and detecting the optical film 01 spline, in which the direction in which the optical film 01 spline microstructure 01a extends is perpendicular to the paper surface; Figure 6 (b) is a side view structural schematic diagram for fixing and detecting the optical film 01 spline, in which the direction in which the optical film 01 spline microstructure 01a extends is parallel to the paper surface.
[0090] Example 2
[0091] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0092] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0093] The transparent PET protective film 02 is a silicone-based PET protective film 02 (Penglin PLSAT-PAD04), the base material (transparent protective film layer) of the silicone-based PET protective film 02 is 50um, and the thickness of the adhesive layer 02b is 10um.
[0094] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0095] 2-9. Same as Example 1.
[0096] This embodiment is the same as the first embodiment except that the thickness of the adhesive layer 02b of the silicone PET protective film 02 is 10 um, which is different from the first embodiment.
[0097] Example 3
[0098] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0099] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0100] The transparent PET protective film 02 is a silicone-based PET protective film 02 (Penglin PLSAT-PAD04), the base material (transparent protective film layer) of the silicone-based PET protective film 02 is 50um, and the thickness of the adhesive layer 02b is 15um.
[0101] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0102] 2-9. Same as Example 1.
[0103] This embodiment is the same as the first embodiment except that the thickness of the adhesive layer 02b of the silicone PET protective film 02 is 15 um, which is different from the first embodiment.
[0104] Example 4
[0105] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0106] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0107] The transparent PET protective film 02 is a silicone-based PET protective film 02 (Penglin PLSAT-PAD04), the base material (transparent protective film layer) of the silicone-based PET protective film 02 is 50um, and the thickness of the adhesive layer 02b is 20um.
[0108] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0109] 2-9. Same as Example 1.
[0110] This embodiment is the same as the first embodiment except that the thickness of the adhesive layer 02b of the silicone PET protective film 02 is 20 um, which is different from the first embodiment.
[0111] Example 5
[0112] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0113] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0114] The transparent PET protective film 02 is a polyurethane-based PET protective film 02 (Stic 12154C), the base material (transparent protective film layer) of the polyurethane-based PET protective film 02 is 50um, and the thickness of the adhesive layer 02b is 5um.
[0115] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0116] 2-9. Same as Example 1.
[0117] This embodiment is the same as Embodiment 1 except that the silicone-based PET protective film 02 in Step 1 is replaced by a polyurethane-based PET protective film 02 .
[0118] Example 6
[0119] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0120] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0121] The transparent PET protective film 02 is a polyurethane-based PET protective film 02 (Stic 12154C), the base material (transparent protective film layer) of the polyurethane-based PET protective film 02 is 50um, and the thickness of the adhesive layer 02b is 10um.
[0122] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0123] 2-9. Same as Example 1.
[0124] This embodiment is the same as Embodiment 2 except that the silicone-based PET protective film 02 in Step 1 is replaced by a polyurethane-based PET protective film 02 .
[0125] Example 7
[0126] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0127] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0128] The transparent PET protective film 02 is a polyurethane-based PET protective film 02 (Stic 12154C), the base material (transparent protective film layer) of the polyurethane-based PET protective film 02 is 50um, and the thickness of the adhesive layer 02b is 15um.
[0129] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0130] 2-9. Same as Example 1.
[0131] This embodiment is the same as Embodiment 3 except that the silicone-based PET protective film 02 in step 1 is replaced by a polyurethane-based PET protective film 02 .
[0132] Example 8
[0133] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0134] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0135] The transparent PET protective film 02 is a polyurethane-based PET protective film 02 (Stic 12154C), the base material (transparent protective film layer) of the polyurethane-based PET protective film 02 is 50um, and the thickness of the adhesive layer 02b is 20um.
[0136] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0137] 2-9. Same as Example 1.
[0138] This embodiment is the same as Embodiment 4 except that the silicone-based PET protective film 02 in step 1 is replaced by a polyurethane-based PET protective film 02.
[0139] Example 9
[0140] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0141] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0142] The transparent PET protective film 02 is an acrylic PET protective film 02 (Fantek FC2514L), the base material (transparent protective film layer) of the acrylic PET protective film 02 is 50um, and the thickness of the adhesive layer 02b is 5um.
[0143] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0144] 2-9. Same as Example 1.
[0145] This embodiment is the same as Embodiment 1 except that the silicone-based PET protective film 02 in step 1 is replaced by an acrylic-based PET protective film 02 .
[0146] Example 10
[0147] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0148] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0149] The transparent PET protective film 02 is an acrylic PET protective film 02 (Fantek FC2514L), the base material (transparent protective film layer) of the acrylic PET protective film 02 is 50um, and the thickness of the adhesive layer 02b is 10um.
[0150] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0151] 2-9. Same as Example 1.
[0152] This embodiment is the same as Embodiment 2 except that the silicone-based PET protective film 02 in step 1 is replaced by an acrylic-based PET protective film 02 .
[0153] Embodiment 11
[0154] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0155] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0156] The transparent PET protective film 02 is an acrylic PET protective film 02 (Fantek FC2514L), the base material (transparent protective film layer) of the acrylic PET protective film 02 is 50um, and the thickness of the adhesive layer 02b is 15um.
[0157] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0158] 2-9. Same as Example 1.
[0159] This embodiment is the same as Embodiment 3 except that the silicone-based PET protective film 02 in step 1 is replaced by an acrylic-based PET protective film 02 .
[0160] Example 12
[0161] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0162] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0163] The transparent PET protective film 02 is an acrylic PET protective film 02 (Fantek FC2514L), the base material (transparent protective film layer) of the acrylic PET protective film 02 is 50um, and the thickness of the adhesive layer 02b is 20um.
[0164] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0165] 2-9. Same as Example 1.
[0166] This embodiment is the same as Embodiment 4 except that the silicone-based PET protective film 02 in step 1 is replaced by an acrylic-based PET protective film 02 .
[0167] Comparative Example 1
[0168] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0169] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0170] The transparent PET protective film 02 is a silicone-based PET protective film 02 (Stick SDK2194X) with extremely low viscosity. The base material (transparent protective film layer) of the PET protective film 02 is 50um thick, and the thickness of the adhesive layer 02b is 5um.
[0171] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0172] 2-9. Same as Example 1.
[0173] This embodiment is the same as Embodiment 4 except that the silicone-based PET protective film 02 in step 1 is replaced with a silicone-based PET protective film 02 with extremely low viscosity.
[0174] Comparative Example 2
[0175] A sample preparation method for analyzing the morphology of a cross-sectional microstructure 01a of an optical film 01, the sample preparation method comprising:
[0176] 1. Take a piece of optical film 01 sample with a size of 200mm*300mm, a piece of transparent PET protective film 02 with a size of 180mm*270mm, and a piece of transparent glass with a size of 300mm*500mm with a flat and clean surface. The structural diagram is as follows: Figure 1 shown.
[0177] The transparent PET protective film 02 is a silicone-based PET protective film 02 (Stick SDK8105G) with high viscosity. The base material (transparent protective film layer) of the PET protective film 02 is 50um thick, and the thickness of the adhesive layer 02b is 5um.
[0178] The transmittance of the transparent protective film layer of the PET protective film 02 is greater than 89%, and the haze is less than 2%.
[0179] 2-9. Same as Example 1.
[0180] This embodiment is the same as Embodiment 4 except that the silicone-based PET protective film 02 in step 1 is replaced with a silicone-based PET protective film 02 with higher viscosity.
[0181] Test Example 1
[0182] According to the experimental steps of Examples 1 to 12 and Comparative Examples 1 and 2, the optical film 01 sample to be tested is coated and cut into 6 strips of the same size (numbered 1#, 2#, 3#, 4#, 5# and 6#), wherein:
[0183] (1) Three sample strips: Use the above-mentioned fixture to prepare the optical film 01 to obtain the sample to be tested, and use a Keyence microscope to perform morphology analysis. Record the data obtained from the three sample strip tests and the clarity of the microscopic morphology.
[0184] (2) The other three specimens were tested for 180° peeling force according to the national standard GB2792-2014. The relevant data were recorded and summarized in Tables 1 and 2.
[0185] Table 1:
[0186]
[0187]
[0188] Table 2:
[0189]
[0190]
[0191]
[0192] As can be seen from the above, the PET protective film 02 of the silicone or polyurethane system used in Examples 1-8 has good air-venting properties, and after coating, the orientation of the underlying microstructure 01a can be easily distinguished, so as to improve the accuracy of cutting the extending direction of the microstructure 01a. Furthermore, the silicone system with a larger refractive index deviation from the resin forming the microstructure 01a is preferred, and the adhesive layer 02b and the underlying microstructure 01a are easier to identify under a microscope.
[0193] Examples 9 to 12 use an acrylic PET protective film 02, which easily introduces air during the bonding process, affecting the identification of the orientation of the microstructure 01a under a microscope, and easily causing orientation deviation of the microstructure 01a during cutting, making the cross-section of the microstructure 01a obtained by cutting non-target cross-section, resulting in sample preparation errors.
[0194] Comparative Examples 1 and 2 are respectively when the 180° peeling force of the protective film is too low or too high, which is also easy to cause sample preparation problems. When the 180° peeling force of the protective film is too low, the protective film is easy to peel off or shift during sample preparation, cutting and transfer, and it is possible that part of the microstructure 01a is damaged. In addition, when the 180° peeling force is too high, the protective film is easy to partially remain on the surface of the microstructure 01a to form contamination, making it difficult to identify the parameters of the microstructure 01a.
[0195] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A sample preparation method for optical film cross-section microstructure morphology analysis, characterized in that: The sample preparation method comprises: S1: Provide the optical film sample and PET protective film to be tested; S2: peeling off the release layer of the PET protective film, and then laminating the adhesive surface of the PET protective film with the microstructure surface of the optical film sample to be tested to obtain a coated sample to be tested; The PET protective film comprises a transparent protective film layer, a glue layer and a release layer arranged in sequence; The transmittance of the transparent protective film layer of the PET protective film is greater than 89%, and the haze is less than 2%. The adhesion of the PET protective film to the attached test sample is 3 to 25 gf / 25 mm; S3: confirm the extension direction of the microstructure on the coated sample by microscopic observation, and cut along the extension direction of the microstructure to obtain the optical film strip; S4: The optical film strip is attached to the cutting pad and fixed, and then two L-shaped fixing brackets are fixed above the optical film strip; the position of one of the L-shaped brackets is adjusted, and the angle between the blade and the film is adjusted to 90°. A 1kg weight is used to quickly smash down from top to bottom at a position about 5 to 10 cm above the blade, and the acceleration of the blade is 2.5-5cm / s 2 , obtaining the cut optical film splines; During the cutting, the transparent protective film layer is arranged below the optical film sample to be tested; S5: Peeling off the transparent protective film layer to obtain an optical film strip having a cross-sectional microstructure.
2. The sample preparation method for optical film cross-section microstructure morphology analysis according to claim 1, characterized in that: The optical film sample to be tested includes any one of a 3D grating film with a microstructure, a wide-viewing angle film, a light-homogenizing film, and a brightness-enhancing film.
3. The sample preparation method for optical film cross-section microstructure morphology analysis according to claim 1, characterized in that: The transparent protective film layer of the PET protective film has a thickness of 38 to 100 μm.
4. The sample preparation method for optical film cross-section microstructure morphology analysis according to claim 1, characterized in that: The adhesive layer thickness of the PET protective film is 5 to 20 μm.
5. The sample preparation method for optical film cross-section microstructure morphology analysis according to claim 1, characterized in that: The adhesive system of the PET protective film is one of acrylic, polyurethane or silicone systems.
6. The sample preparation method for optical film cross-section microstructure morphology analysis according to claim 5, characterized in that: The adhesive system of the PET protective film is one of polyurethane or silicone systems; Preferably, the adhesive system of the PET protective film is a polyurethane system.
7. The sample preparation method for optical film cross-section microstructure morphology analysis according to claim 1, characterized in that: After the PET protective film is attached to the optical film sample to be tested, the peeling force at 180° is 3-25 gf / 25 mm.
8. The sample preparation method for optical film cross-section microstructure morphology analysis according to claim 1, characterized in that: The size of the optical film strip is 100 mm*10 mm.
9. Application of the sample preparation method for optical film cross-sectional microstructure morphology analysis as described in any one of claims 1 to 8 in optical film cross-sectional microstructure morphology analysis.
Citation Information
Patent Citations
Optical film, laminated film utilizing same, and method of manufacturing optical film
CN109791244A
Bubble defect analysis method based on optical transparent adhesive tape
CN111474034A
Method for improving morphology of metal electrode
CN112768353A
Observation method based on shooting of cross-section diagram of graphene oxide carbon nanotube composite film
CN114813807A
Optical film laminate, optical display device using the same, and transparent protective film
CN115576046A